Modelling and Observation of PEM Fuel-Cell Systems: Application to the Automobile Transport Field - Zakaria, BAROUD; Atallah, BENALIA (Université de Laghouat , Bibliothèque centrale, 2018)
Nowadays, the Proton Exchange Membrane Fuel Cell (PEMFC) are considered as one of the most efficient solutions for energy production to face both serious environmental pollution and energy crisis around the world. PEMFC are electrochemical devices that produce electricity, water, and heat from hydrogen and oxygen. Moreover, the PEMFC, also called Solid Polymer Fuel Cell (SPFC), are used in a wide range of applications, with advantages such as high efficiency, low weight, low pollution and low operation temperature, features that allow fast starting times in the PEMFC systems. However, for applications that require the tracking of rapid load changes, such as transport applications, the PEMFC must be able to follow rapid load changes and also able to be adapted to varying operating conditions. As a result, advanced control strategies must be integrated to ensure that the flows entering the PEMFC stack are sufficient and well-conditioned. The first contribution of thesis is interested in the control of the PEMFC air supply system. The control objective is to regulate fast and efficiently the oxygen depleted in the cathode channel in order to avoid both oxygen starvation and saturation phenomena. This problem has been addressed using two controllers. The first control strategy, known as hybrid fuzzy PID control, is separated into three parts: fuzzy control, fuzzy-based self-tuned PID control, and fuzzy selector. The second control strategy, known as Second-Order Sliding-Mode (SOSM) twisting control, used an off-line tuning procedure to tune the controller parameters. Their performances are validated through extensive computer simulations. However, this is a challenging task because both two control strategies require knowing the exact value of Oxygen Excess Ratio (OER), which depends on internal variables such as the air pressure in the supply manifold and the partial pressures of both oxygen and nitrogen in the cathode. This means they should be used further sensors for measurements that increase both the overall system complexity and the cost while decreasing the efficiency of the fuel-cell system. Therefore, observers using only the measurements of available states become a cheaper and attractive solution. The second contribution of thesis presented an algebraic-observer-based output-feedback controller, which is based on both algebraic differentiation and sliding-mode control approaches. At first, an algebraic estimation approach is used to reconstruct the OER based on a robust differentiation method. Then, the SOSM twisting controller presented in the first part of the thesis was adopted. The performance of the proposed algebraic-observer-based output-feedback controller is analyzed through simulations. Results show that the proposed approach properly estimates and regulates the OER in finite time.